The Effects of Teaching Style on Creativity - Leathers, Fran (Valdosta State University, 2001)
In an attempt to associate student creativity and the use of interactive software, an action research project was designed and implemented in an elementary school. The action research compared the effect of using two types of instruction, Discovery Learning and Direct Teacher Instruction, when teaching 5th grade students to use MicroWorlds software in order to create a multimedia presentation. Creativity assessment instruments were used to measure creativity levels of participants both pre-project and post-project. Projects themselves were also evaluated. Of the 36 gifted fifth graders who participated, there were thirteen in the Discovery Group, fourteen in the Direct-Instruction Group, and nine in a group who had no exposure to MicroWorlds software. The presentations of the Direct-Instruction Group were judged by the researcher and two other gifted education teachers to be more creative than the other two groups; however, the instruments employed to compare students' overall creative ability at the beginning and the end of the project did not show significant change despite the instructional style. Unexpected findings exclusively related to the Discovery Group included an increase in learner confidence, growth in learner independence, and a heightened sense of enjoyment related to discovering how to operate the software.
Keywords: Creativity; Interactive software; Discovery learning; Direct teacher; Educational technology; Teaching--Aids and devices; Computer-assisted instruction